Performance evaluation of subsurface drainage system under unsteady state flow conditions in coastal saline soils of Andhrapradesh, India - Chandra, S. Ramesh, author; Shyamsundar, K., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
The performance of an executed subsurface drainage system was evaluated under unsteady flow conditions. The impulse-response relation has been studied for two different conditions of drain spacings, namely, the executed drain spacing based on steady state flow conditions and the drain spacing proposed on unsteady state flow conditions, incorporating the effects of drainable porosity. It is found rational to use the "Dezeeuw-Hellinga model" for prediction of impulse response relations in terms of temporal water table fluctuations against rainfall — recharge under unsteady state flow conditions. The responses of a sub-surface drainage system for the impulse of incessant rainfall have been studied. The values of calculated drain spacings varied from 11 to 15 m. However, due to economic conditions, the practical drain spacings of the layout have been fixed at wider value of 35m and 55m. It is found that the drain spacings adopted for unsteady state flow conditions might have resulted in a better performance of the drains compared to steady state drain spacing as depicted by Dezeeuw-Hellinga model run. The drainable porosity being the vital parameter in an unsteady state equation, the Dezeeuw-Hellinga model was also used for varying levels of drainable porosity under given drain spacing conditions. Generally, the reference drainable porosity value is taken as 10 per cent for most of the drainage studies and the influence on drain outflows were compared for an increased value of 20 per cent and decreased value of 5 per cent, since the drainable porosity value in the study area varied from 5 to 20 per cent. It was found that the change in drainable porosity significantly influence the drain performance as depicted by Dezeeuw-Hellinga model run over all the standard week of year. The executed sub-surface drainage system has been found satisfactory in bringing down the soil salinity levels to desirable limits below 4 dSm-1. The executed sub-surface drainage system has also resulted in appreciable crop productivity improvements in the locality.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.